(3MOhO GdCeQGVs - (3CQRGfj, eMeO CcHQ YQa eMeOs
(3ChdgG (B:s
(3GdMeO ddg GdefYe GdecQeCeG HYO ajbhdeMeO CcHQ YQa eMeO CQRGfj deG aQZJ ef JQLeI TQM GdCSHGH hGdYdGeGJCQOJ Cf CLeY MOhO GdCeQGVs
(3BNQgG (B:s
(3GdjfHY HGdaJM hGdfhf hGdYjf GdegedI hQe YXje aj GdedJMeI hGdCLaGf gPG EPG YQV ddcHGQ jSei Hg hEPG YQV ddUZGQ jSei HGdhQOjfL ceG eQ JMbjbg aj GdOQOjfLs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdWHs